A Study on the ESG Institutional Orientation of Vietnam's National Parks Based on Policy Texts and Its Implications - Cao Hy Yen; Bui Thi Huong Nguyet (PT FORMOSA CENDEKIA GLOBAL, 2026)
The ESG (Environmental, Social, Governance) framework has become an important tool for measuring the sustainability of public governance. Based on 294 core policy texts, it constructs a policy coding framework encompassing the three dimensions of E, S, and G, and systematically traces the evolution of Vietnam's national park governance model from 1962 to 2026. The findings reveal that: (1) Vietnam's national park policy system has undergone a profound transformation from administrative-command orientation to law-based and collaborative governance. (2) In terms of ESG dimensional distribution, it exhibits a structural characteristic characterized by a high level of environmental (E) performance, continuously strengthened governance (G), and a deepening evolution of the social (S) dimension. (3) In terms of policy instruments, institutional arrangements, spatial planning, and the Payment for Forest Environmental Services (PFES) mechanism constitute the three pillars of its governance system. (4) Through a comparative study with China's national park governance model, the research finds that, based on similar stages of development, China and Vietnam have taken differentiated paths: China tends toward a strong central state-led management model primarily relying on fiscal investment, while Vietnam exhibits a central-local power-sharing characteristic and possesses unique advantages in market-based ecological compensation mechanisms such as PFES. Based on Vietnam's experience, this study proposes a protected area governance model characterized by